2015
DOI: 10.1016/j.ydbio.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Dpp/Gbb signaling is required for normal intestinal regeneration during infection

Abstract: Maintaining tissue homeostasis is a critical process during infection and inflammation. Tissues with a high intrinsic turnover, such as the intestinal epithelium, must launch a rapid response to infections while simultaneously coordinating cell proliferation and differentiation decisions. In this study, we searched for genes required for regeneration of the Drosophila intestine, and thereby affecting overall organism survival after infection with pathogenic bacteria. We found that Dpp/Gbb (BMP) signaling is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 49 publications
5
82
1
1
Order By: Relevance
“…During embryonic gut formation Dpp is required in a complex feedback, both within and between tissue layers, to maintain the correct patterning of homeotic gene expression during midgut morphogenesis [46,47]. In the Drosophila adult gut, Dpp has multiple complex roles in the regulation of ISCs in both an autocrine and paracrine mode [48][49][50][51][52][53]. Additionally, the TGF-β/ activin pathway acts as a carbohydrate-sensing mechanism in the adult midgut to regulate digestive enzyme expression [54].…”
Section: Discussionmentioning
confidence: 99%
“…During embryonic gut formation Dpp is required in a complex feedback, both within and between tissue layers, to maintain the correct patterning of homeotic gene expression during midgut morphogenesis [46,47]. In the Drosophila adult gut, Dpp has multiple complex roles in the regulation of ISCs in both an autocrine and paracrine mode [48][49][50][51][52][53]. Additionally, the TGF-β/ activin pathway acts as a carbohydrate-sensing mechanism in the adult midgut to regulate digestive enzyme expression [54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that BMP signaling is activated in ISCs, enteroblasts and enterocytes, and that it plays several roles, including regulation of ISC division and differentiation, enterocyte survival and copper cell differentiation (Ayyaz et al, 2015;Guo et al, 2013;Li et al, 2013a,b;Tian and Jiang, 2014;Zhou et al, 2015). Our RT-qPCR analysis did not detect any difference in the mRNA levels of dpp and glass bottom boat (gbb), which encode ligands of the BMP pathway, between the wild-type and Sulf1 mutant midgut samples (Fig.…”
Section: P1mentioning
confidence: 99%
“…Conversely, hyperactivation of either pathway leads to ISC hyperproliferation (Lin et al, 2008) (Lee et al, 2009) (Jiang et al, 2011) (Buchon et al, 2010) (Cordero et al, 2012b) (Cordero et al, 2012a). Multiple sources of the BMP ligands Dpp and Gbb, maintain intestinal homeostasis by constraining ISC proliferation (Tian and Jiang, 2014) (Li et al, 2013b) (Zhou et al, 2014). Recently, Hedgehog (Hh) signalling has emerged as a positive regulator of basal ISC proliferation in the midgut.…”
Section: Basal Homeostatic Self-renewal Of the Adult Drosophila Midgutmentioning
confidence: 99%
“…Finally, activation of DPP/BMP signalling is required for the return to homeostasis after repair of the damage epithelium has been achieved (Zhou et al, 2014) (Guo et al, 2013).…”
Section: Intestinal Stem Cell Homeostasis During Tissue Regenerationmentioning
confidence: 99%